2009
DOI: 10.1099/ijs.0.005512-0
|View full text |Cite
|
Sign up to set email alerts
|

Gracilimonas tropica gen. nov., sp. nov., isolated from a Synechococcus culture

Abstract: An irregular, long, rod-shaped marine bacterium, designated CL-CB462T , was isolated from a Synechococcus culture, which was established from surface water from the tropical Pacific Ocean. The physiological and biochemical features, fatty acid profile and phylogenetic position based on 16S rRNA gene sequences were investigated for the novel strain. Phylogenetic analysis of the 16S rRNA gene sequence showed that the closest relatives of strain CL-CB462 T wereBalneola vulgaris and Balneola alkaliphila. Strain CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“… All data are from the original descriptions (Alfredsson et al, 1988; Antón et al, 2002; Choi et al, 2009; Vaisman and Oren, 2009; Marteinsson et al, 2010; Park et al, 2011, 2013; Urios et al, 2006, 2008; Makhdoumi-Kakhki et al, 2012; Wang et al, 2012, 2013a,b; Cho et al, 2013) except for the polar lipids of Salinibacter ruber (Corcelli et al, 2004) and Salisaeta longa (Baronio et al, 2010). Question marks indicate missing information.…”
Section: Resultsmentioning
confidence: 99%
“… All data are from the original descriptions (Alfredsson et al, 1988; Antón et al, 2002; Choi et al, 2009; Vaisman and Oren, 2009; Marteinsson et al, 2010; Park et al, 2011, 2013; Urios et al, 2006, 2008; Makhdoumi-Kakhki et al, 2012; Wang et al, 2012, 2013a,b; Cho et al, 2013) except for the polar lipids of Salinibacter ruber (Corcelli et al, 2004) and Salisaeta longa (Baronio et al, 2010). Question marks indicate missing information.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the heterotrophic consorts are representatives of OTUs abundant within the Hot Lake mat community (Lindemann et al, 2013) and all are assigned to taxa frequently found in hypersaline cyanobacterial mats (e.g., Halomonas, Marinobacter , and Rhodobacteraceae ; Jonkers and Abed, 2003). Phylogenetic near neighbors of these members have been frequently observed as epibionts of Trichodesmium consortia in the open ocean (Hmelo et al, 2012), cyanobacterial aggregates from the Baltic Sea (Tuomainen et al, 2006), and isolates from cyanobacterial cultures (Choi et al, 2009; Hube et al, 2009; Shi et al, 2009). Furthermore, our consortia contain multiple members of the Roseobacter clade of Alphaproteobacteria , which are known to be frequent members of phototrophic mats and consorts of marine photoautotrophs (Buchan et al, 2005; Brinkhoff et al, 2008; Mayali et al, 2008; Wagner-Döbler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a novel moderately halophilic bacterium with characteristics similar to members of the genus Aliifodinibius is reported. This research also led to the proposal of a novel family Balneolaceae, encompassing four genera, namely Fodinibius, Aliifodinibius, Gracilimonas (Choi et al, 2009) and Balneola (Urios et al, 2006). During a study into the diversity of halophilic bacteria in marine solar saltern environments, a novel facultatively anaerobic, red, non-motile, Gram-stain-negative bacterial strain, designated 2W32 T , was isolated at 37 C on modified marine agar 2216 (MA) (consisting of distilled water with the following additions (all g l Province, China.…”
mentioning
confidence: 98%
“…Searches via the BLAST program revealed that the novel isolate had the highest similarity to A. sediminis DSM 21194 T (94.6 %) (Wang et al, 2013a), followed by Aliifodinibius roseus KCTC 23442 T (94.4 %) (Wang et al, 2013a), F. salinus DSM 21935 T (93.6 %) (Wang et al, 2012), Gracilimonas tropica CL-CB462 T (88.6 %) (Choi et al, 2009), Gracilimonas rosea CL-KR2 T (88.5 %) (Cho et al, 2013), Gracilimonas mengyeensis YIM J14 T (87.5 %) (Wang et al, 2013b), Balneola vulgaris 13IX/A01/164 T (86.4 %) (Urios et al, 2006) and Balneola alkaliphila CM41_14b T (86.3 %) (Urios et al, 2008). Except for the above-mentioned strains, published sequences from other strains showed less than 83.0 % 16S rRNA gene sequence similarity with strain 2W32 T .…”
mentioning
confidence: 99%